Práticas pedagógicas de professores que ensinam matemática nos anos finais do ensino fundamental - Silva, Élio Rubens de Freitas (2021)
The teaching activity challenges the teacher to use differentiated pedagogical practices that contribute to achieving student learning. Thus, the general goal of this research is to understand the pedagogical practices of teachers who teach mathematics in the late years of Elementary School. It figures as a qualitative approach, in which we are theoretically based on Bogdan and Biklen, Chizotti, Richardson, among others. To answer our research problem, we define as research context, a State School in the city of Rondonópolis-MT, situated in an urban area, to be called is this research as Beta School. As research subjects, we choose four teachers, who work in the late years of Elementary School and teach mathematics at the school participating in the research. As tools for data production, we use teacher profile questionnaires and semi structured interviews, as well as documentary analysis of the Political Pedagogical Project. The problem of this research is guided by the following question: what are the pedagogical practices developed by mathematics teachers in the late years of Elementary School? To discuss the conceptions of pedagogical practice and reflexive practice, we refer to the theorists: Caldeira and Zaidan, Franco, Sacristán, Veiga, Fernandes, Verdum, Schön, Pimenta, among others. To discuss the teaching of mathematics in Basic Education, we dialog with D’Ambrósio, Lorenzato, PCN, Fiorentini, Onuchic, Santos, BNCC, among others. To interpret and analyze the data, based on the theoretical framework mentioned above and the data collected, we develop four dimensions of analysis: Pedagogical practices, Planning Development; Mathematics teaching, and Teachers’ professional experience. Data analysis and interpretation allow us to consider that the conceptions of pedagogical practices of the teachers participating in the research present many concepts that they use when acting in the classroom, as a result, at the same time, of their daily reality, their needs, resources, and limitations. On planning development, based on the conceptions of the teachers surveyed, we could verify that the planning development must be in line with the process of building the school curriculum, and must be in line with the school Political Pedagogical Project. Teachers understand that the mathematics knowledge acquired during basic training was not enough to support their pedagogical practices to teach mathematics to the late years of Elementary School. The results of this research indicate that the development of pedagogical practices of teachers in the late years of Elementary School is grounded in their common sense conceptions, without being based on any theoretical framework. The results show a pedagogical practice that differentiates itself by using simple learning methodologies and strategies that can be used to maximize the teaching-learning process of the students in the late years of Elementary School.